ENGLISH BORROWING PATTERNS FOUND IN KOMPAS.COM ARTICLES RELATED TO YOUTH PLEDGE DAY ON 28 OCTOBER 2014 - TAMARA, PINTA DIANING (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: morphology, word-formation process, borrowing, English borrowing patterns, Kompas.com, Youth Pledge DayBorrowing is one of language phenomena that occur because of the influence of other languages. Borrowing is the taking over of words from other languages. It is easily found everywhere even in daily conversation or in the article of newspaper. This study observes the use of borrowing and its pattern that is found in Kompas.com articles since Kompas.com is the most popular Indonesian news portal that uses best Indonesian diction. The aims of this study are: 1) to find out the borrowings found in Kompas.com articles related to Youth Pledge Day, 2) to know the patterns of borrowing found in Kompas.com articles related to Youth Pledge Day, and 3) to find the equal Indonesian word of borrowing found in Kompas.com.This study applied descriptive qualitative approach because the writer conducted the study by analyzing and interpreting the content of the texts. The writer used the theory of Baker & Jones (1998) about the patterns of borrowing which are loanword, loanshift, and loanblend. The writer took 10 articles related to Youth Pledge Day on 28 October 2014 in Kompas.com as the data. The writer collected the data and categorized them into each pattern.The findings resulted that from three patterns, there were only two patterns used, namely loanword and loanblend. Most of the data were loanwords. Besides, nouns were mostly found according to the categorization of  part of speech. From 91 borrowings found, there were 50 borrowings that had equal words in Indonesian.The writer suggests the next writer who wants to make further study in the same field to analyze borrowing from different sources. The writer also suggests the next writers to investigate the reason why the writers of the articles prefer to use borrowing words rather than Indonesian words.